PENGARUH KOMPETENSI PROFESIONALISME GURU TERHADAP PRESTASI BELAJAR BAHASA INDONESIA SISWA DI SMPN 1 KILO - Kasdin Kasdin; Johan Mahyudi; Burhanuddin Burhanuddin (Universitas Muhammadiyah Mataram, 2023)
This study aims to describe the picture of professional competence, the role of teachers and the influence of teacher professionalism on learning achievement Indonesian students at SMPN 1 Kilo. Data were collected using survey and experimental methods. The survey method to require a sufficient number of respondents for the validity of the findings to be achieved properly. Experimental method to explain the causal relationship between one variable and another (variable x and variable y). The results showed that the picture of teacher professional competence results of r calculation value and r table value with 10 items can be classified into the first two parts, 5 items are declared valid with a percentage of 50%, and 5 items are declared invalid with a percentage of 50%, while the role of the teacher can Indonesian be seen the results of the r calculation value and the r table value with 12 items classified into the first two parts, 5 items are declared valid with a percentage of 41%, while 7 items are declared invalid with a percentage of 58%.